Chaoid Cinema Deleuze & Guattari and the Topological Vector of Silence - Gardner, Colin 1952- (Edinburgh University Press, 2022)
A Deleuzian analysis of the role of silence as chaotic interstice in sound filmApplies Deleuze and Guattari's Chaoids to cinema for the first timeUses case studies from world cinemas - Iran, Brazil, France, UK, U.S.A., Germany - to explore different philosophical, cultural and historical contextsBrings together Film-Philosophy, Comparative Literature (Lettrism, Iranian poetry, Joyce and Ponge), Film History and radical movements from the 1960s and '70sExpanding on a burgeoning area in contemporary film studies that explores visual and aural absences and interstices in film narrative, this book explores silences in the soundtrack - not ambient silence or so-called 'room tone' but complete sound drop-outs, as if the film projector had broken down, thereby jolting the audience out of their passive relationship to the screen, forcing them to become aware of their surroundings and the material apparatus of film as a mechanical device.Drawing on Deleuze and Guattari's concept of Chaoids, which are various organizations of chaos through the different disciplines of science, philosophy and art, this book uses silence to pursue a variety of vectors that open up the surface plane of art (in this case cinema) to discover different philosophical (and by extension, political) singularities and multiplicities.